War and state building in the Middle East - Schwarz, Rolf (Governance and international relations in the Middle East, 2012)
Introduction -- Understanding state making -- Iraq: from rentier state to failed state -- Jordan: rentierism and state survival -- The gulf states: from tribal sheikhdoms to sustainable states -- State failure and peace building